2023
DOI: 10.1038/s41467-023-39885-5
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont-host interactome mapping reveals effector-targeted modulation of hormone networks and activation of growth promotion

Rory Osborne,
Laura Rehneke,
Silke Lehmann
et al.

Abstract: Plants have benefited from interactions with symbionts for coping with challenging environments since the colonisation of land. The mechanisms of symbiont-mediated beneficial effects and similarities and differences to pathogen strategies are mostly unknown. Here, we use 106 (effector-) proteins, secreted by the symbiont Serendipita indica (Si) to modulate host physiology, to map interactions with Arabidopsis thaliana host proteins. Using integrative network analysis, we show significant convergence on target-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 89 publications
1
26
0
Order By: Relevance
“…Thus, the 60 human proteins targeted by effectors from four or even more commensal strains are subject to effector convergence and may be of general importance for human microbe-host interactions. Together with our recently published plant-symbiont interaction data 31 , these data suggest that convergence has evolved as a universal feature of effector-host interactions independent of the microbial lifestyle and kingdom of the host organism.…”
Section: Mainsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, the 60 human proteins targeted by effectors from four or even more commensal strains are subject to effector convergence and may be of general importance for human microbe-host interactions. Together with our recently published plant-symbiont interaction data 31 , these data suggest that convergence has evolved as a universal feature of effector-host interactions independent of the microbial lifestyle and kingdom of the host organism.…”
Section: Mainsupporting
confidence: 67%
“…The presence of T3SS in human commensal microbes has been noticed previously and was speculated to mediate crosstalk between the intestinal microbiota and the human host 66,67 . Here, we provide evidence that, analogous to the plant kingdom 31,68 , also in the human gut T3SS and effectors function in commensal microbe-host interactions and modulate immune signaling. Thus, effector secretion appears to be used universally by Pseudomonadota to mediate interactions with multicellular eukaryotes independently of the lifestyle of the microbe.…”
Section: Discussionmentioning
confidence: 83%
“…It indicated that modulation of hormones is not only involved in colonisation strategies but supports the hypothesis that Si effectors recruit specific proteins of the hormone network to confer beneficial traits. [85] Functional assays confirmed that in addition to targeting hormone related proteins symbiotic effectors alter hormone signalling pathways in planta. Hormone marker assays in protoplasts identified extensive and highly specific hormone signalling modulation by Si effectors.…”
Section: Symbiont Effectors Identify Beneficial Genetic Traits In Hig...mentioning
confidence: 84%
“…[77,89] Our comparative effectome analysis identified Si effectors that shared targets with pathogen effectors and were most likely involved in PTI modification at initial cell colonisation. The majority of symbiotic effectors, however, had exclusive targets [85] which may indicate Si effector-host protein interactions involved in the activation of beneficial pathways. A subsequent annotation analyses revealed an abundant function of Si effectors in interacting with hormone pathways.…”
Section: Effectors Are Required In Beneficial Symbiosismentioning
confidence: 99%
See 1 more Smart Citation